Examining the Efficacy of Fair Trade Eco-Labeling on Environmental Sustainability and Human Rights in Developing Countries - Overbeek, Ashley (Consilience, 2015)
Through the lens of political ecology, the idea of alternative consumption, as defined by Bryant et al, is the consumption of more sustainable products with eco-labels alerting consumers about the benefits of purchasing said product instead of traditional products. Here, I examine the efficacy of Fair Trade certification on environmental sustainability and human rights in developing countries. Benefits accrued to Fair Trade, namely that certification informs consumers about environmental and social issues occurring in developing countries, provides consumers an option for “alternative”, more sustainable consumption, encourages businesses to develop in a more sustainable manner, and also may provide premiums that support environmental conservation and human well-being in developing countries or traditionally rentier-states. However, several drawbacks of Fair Trade certification and alternative consumption also have been noted, namely the concerns about corporate greenwashing, as well as the potential for creating a moral hazard for consumers who feel as though they are making a difference by simply perpetuating a neo-liberal capitalistic culture that oppresses those in developing countries in the first place. In addition, the definite Edenization of the rainforest can have arguably positive and negative benefits on the environmental and social aspects of developing countries. This paper will also examine the long-term effects of green marketing in the global North on the perceptions of the South as a place of unaltered wilderness and pristine ecosystems separate from the social struggles of human society. This paper argues that Fair Trade and alternative consumption has its benefits and constraints/limitations, but overall has greatly improved the plight of developing countries. Inherently, alternative consumption subscribes to neo-liberal systems and capitalistic culture, yet given we all must consume and alternative consumption captures a large audience and corporations with considerable purchasing power, Fair Trade certification and alternative consumption may be an effective means of consumptive change within the system.